Audio stimulation athletes with visual impairments in running - Andrii Yefremenko; Svyatoslav Koval; Viktor Pavlenko; Tetiana Shutieieva; Yaroslav Kraynik; Svetlana Pyatisotskaya (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to reveal differences between the running characteristics of athletes with visual impairment without and with audio stimulation. Objects: athletes with visual impairments (category T13) (boys n=6 and girls n=5). Material and Methods: test No1: running for 4 minutes with a gradual increase in pace; test No2: running for 4 minutes in the tempo of the metronome (140; 150; 160; 170 bpm). Results: Comparison of test results No1 and No2 in the group of young men revealed the reliability of differences (p<0,05) for: the first and fourth minutes of running; average running speed in the second minute. Comparison of the results of tests No1 and No2 in the group of girls revealed the reliability of differences (p<0,05) for: the distance of running in the first minute; average running speed in the first and second minutes. Conclusions: similar physiological reactions were recorded in boys and girls on exercise, which increases in steps, regardless of the method of stimulation. At the same time, there are certain differences in the strategy of movement, depending on the method of stimulation. This confirms the complex effect of the imposed rhythm on the performance of cyclic locomotion. We expected significant differences between running characteristics with and without auditory stimulation. However, a large number of reliable differences between the results, including for boys and girls, were not found. At this stage, we are inclined to think that the selected metronome frequencies are convenient for running with a load that rises stepwise.